Inheritance Rights of Children Born Out of Wedlock in the Perspective of Islamic Law - Pirdaus, Dede Irman; AS, Nurnisaa (Communication in Research and Publications (CRP), 2024)
This study aims to analyze the legal status of illegitimate children from the perspective of Islamic law and civil law in Indonesia, focusing on aspects of lineage, inheritance rights, and legal protection. This study uses a literature study method with descriptive-analytical analysis to compare regulations in Islamic law and positive law. In Islamic law, illegitimate children only have lineage and inheritance rights through the mother and her family, while in civil law, illegitimate children can obtain legal recognition from their parents through a process of recognition or a court decision. This study also highlights the role of the Constitutional Court Decision Number 46/PUU-VIII/2010 which provides further legal protection for illegitimate children, especially regarding civil rights. Although there are fundamental differences in the recognition of lineage and inheritance rights, both legal systems agree on the importance of protecting children's basic rights